The Financial Credit Profile of Low-Income Families Seeking Assets - Julie Birkenmaier; Jamie Curley; Patrick Kelley (Journal of Financial Therapy, 2011)
Individual Development Account (IDA) participants need strong credit histories to access affordable credit for their IDA asset purchase. Using a convenience sample of IDA participants (N = 188) recruited from the St. Louis, MO area, this study presents credit profile data addressing utilization of alternative and mainstream financial services, amount of debt carried, and elements needed to improve credit. This study presents data on the credit profile of IDA participants (N = 188). Compared to national IDA participants, participants in this study had higher incomes, were more educated, and had a higher rate of being “banked.” The sample was not overburdened with their monthly debt. However, participants also utilize higher-cost alternative financial services, such as payday lenders and pawnshops, at similar rates to other low-income families and are beginning their IDA programs with low credit scores and poor credit history. Participant needs for credit assistance is discussed, and practice, policy, and research implications are provided.
Keywords: financial therapy; financial counseling